2020
DOI: 10.3390/electronics9101598
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Effects on OFDM Wireless Links Operating in the Millimeter Wave Regime

Abstract: The development of millimeter wave communication links and the allocation of bands within the Extremely High Frequency (EHF) range for the next generation cellular network present significant challenges due to the unique propagation effects emerging in this regime of frequencies. This includes susceptibility to amplitude and phase distortions caused by weather conditions. In the current paper, the widely used Orthogonal Division Frequency Multiplexing (OFDM) transmission scheme is tested for resilience against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The protocol was adjusted for probabilistic weather forecasts in a communication satellite control loop. Golovachev et al [5] showed the reduction of the bit error rate for the orthogonal frequency division multiplexing (OFDM) communication link applied for millimeter-waves (MMW, 30 GHz-300 GHz) transmission. Bonev et al [6] analyzed rain attenuation measurements collected over four years, working at 11, 15, and 19 GHz, and proposed to improve the rain-prediction model's accuracy coefficients.…”
Section: Related Workmentioning
confidence: 99%
“…The protocol was adjusted for probabilistic weather forecasts in a communication satellite control loop. Golovachev et al [5] showed the reduction of the bit error rate for the orthogonal frequency division multiplexing (OFDM) communication link applied for millimeter-waves (MMW, 30 GHz-300 GHz) transmission. Bonev et al [6] analyzed rain attenuation measurements collected over four years, working at 11, 15, and 19 GHz, and proposed to improve the rain-prediction model's accuracy coefficients.…”
Section: Related Workmentioning
confidence: 99%
“…It is a known protocol adjusted for probabilistic weather forecasts in a communication satellite control loop. Golovachev et al [4] show the reduction of the bit error rate for the orthogonal frequency-division multiplexing (OFDM) communication link applied for millimeter waves (MMW, 30-300 GHz) transmission. Bonev et al [5] analyzed rain attenuation measurements collected over four years, working at 11,15 and 19 GHz, and proposed to improve the rain-prediction model's accuracy coefficients.…”
Section: Related Workmentioning
confidence: 99%
“…Considering rain distortions or urban objects means taking into account that a relationship exists between the input and the output linear depolarizing electric field components, propagating from the raindrop or the scattering objects in the medium. To illustrate the destructive rain phenomenon, it is possible to see the Figure 2e at [ 13 ], and the diagram at [ 9 ]. The effects of these phenomena on wireless communication systems based on orthogonal Dual-Polarization (DP) components, cause a deterioration in system performance, due to the sensitivity of orthogonality between polarized-signals and spatial-paths.…”
Section: Introductionmentioning
confidence: 99%